Interferon gamma-induced protein 10 (IP-10) for the early prognosis of the risk for severe respiratory failure and death in COVID-19 pneumonia. (February 2023) - Samaras, Charilaos; Kyriazopoulou, Evdoxia; Poulakou, Garyfallia; Reiner, Eran; Kosmidou, Maria; Karanika, Ioanna; Petrakis, Vasileios; Adamis, George; Gatselis, Nikolaos K.; Fragkou, Archontoula; Rapti, Aggeliki; Taddei, Eleonora; et al.
Highlights: CRP, IP-10 and TRAIL were compared to suPAR for predicting outcome in COVID-19. IP-10 ≥ 2000 pg/ml predicts equally well to suPAR (sensitivity 85.0 %) Anakinra treatment improved outcomes of patients with IP-10 ≥ 2000 pg/ml. Results of a discovery cohort (n: 534) were validated in a second cohort (n: 364) Abstract: Objectives: Elevated concentrations of soluble urokinase plasminogen activator receptor (suPAR) predict progression to severe respiratory failure (SRF) or death among patients with COVID-19 pneumonia and guide early anakinra treatment. As suPAR testing may not be routinely available in every health-care setting, alternative biomarkers are needed. We investigated the performance of C-reactive protein (CRP), interferon gamma-induced protein-10 (IP-10) and TNF-related apoptosis-inducing ligand (TRAIL) for predicting SRF or death in COVID-19. Methods: Two cohorts were studied; one discovery cohort with 534 patients from the SAVE-MORE clinical trial; and one validation cohort with 364 patients from the SAVE trial including also 145 comparators. CRP, IP-10 and TRAIL were measured by the MeMed Key® platform in order to select the biomarker with the best prognostic performance for the early prediction of progression into SRF or death. Results: IP-10 had the best prognostic performance: baseline concentrations 2000 pg/ml or higher predicted equally well to suPAR (sensitivity 85.0 %; negative predictive value 96.6 %). Odds ratio for poor outcome among anakinra-treated participants of the SAVE-MORE trial was 0.35 compared to placebo when IP-10 was 2, 000 pg/ml or more. IP-10 could divide different strata of severity for SRF/death by day 14 in the validation cohort. Anakinra treatment decreased this risk irrespective the IP-10 concentrations. Conclusions: IP-10 concentrations of 2, 000 pg/ml or higher are a valid alternative to suPAR for the early prediction of progression into SRF or death the first 14 days from hospital admission for COVID-19 and they may guide anakinra treatment. Trial registration. ClinicalTrials.gov, NCT04680949 and NCT04357366.